Language, literacy and diversity : moving words - Stroud, Christopher; Prinsloo, Mastin (London : Routledge, Taylor & Francis Group, 2015)
'Language, Literacy and Diversity brings together researchers who are leading the innovative and important re-theorization of language and literacy in relation to social mobility, multilingualism and globalization. The volume examines local and global flows of people, language and literacy in relation to social practice; the role (and nature) of boundary maintenance or disruption in global, transnational and translocal contexts; and the lived experiences of individuals on the front lines of global, transnational and translocal processes.The contributors pay attention to the dynamics of multilingualism in located settings and the social and personal management of multilingualism in socially stratified and ethnically plural social settings. Together, they offer ground-breaking research on language practices and documentary practices as regards to access, selection, social mobility and gate-keeping processes in a range of settings across several continents: Africa, Asia, the Americas and Europe'--
Includes bibliographical references and index.
Keywords: Literacy; Sociolinguistics; Language and languages -- Study and teaching; Language and languages -- Globalization; Language and culture -- Globalization; Language and languages -- Variation; Multilingualism; Language and education